Sikap Terhadap Konsentrasi Belajar Siswa Pada Mata Pelajaran Fisika di Sekolah Menengah Atas - Puspitasari, Tari Okta; Putri, Yolanda Eka; Yohanes, Yohanes (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
The purpose of this study is to explore the relationship between attitudes and student learning in physics. The research method used is quantitative research with associative design. The research instrument used was a questionnaire. The data analysis technique used is descriptive statistical analysis and inferential analysis. Descriptive statistics used are the mean, median, mode, and standard deviation. Whereas the inferential statistics that can be used is the collaborative test. Based on research that has been done, there is a positive relationship between attitude and concentration in physics at SMAN 8 Jambi City which is also quite strong when viewed from the sig value generated, which is equal to 0.04.